Macroscopic Features of The External Auditory Canal in Patients with Otitis Externa With Otoscopic Examination at The Ent Polyclinic of Tamiang Layang Hospital - Anugerahny, Margaretha Yayu Indah; Mutiasari, Dian (Jurnal Kedokteran Universitas Palangka Raya, 2025)
Otitis externa is one of the most painful types of inflammation is one of the common external auditory canal diseases in clinical practice. Otitis externa is an inflammation of the external auditory canal caused by bacteria, fungi. The aim of this study was to determine the characteristics of otitis externa treated at the ENT polyclinic of Tamiang Layang Hospital in 2022-2023. This study is a descriptive study using a retrospective approach using secondary data, namely medical records of patients diagnosed with otitis externa at the ENT-KL Polyclinic of Tamiang Layang Hospital in 2022-2023. This study had a sample of 335 otitis externa patients. Otitis externa occurs more in women, namely 196 patients (58.5%). The largest age group was 26-45 years, 132 patients (39.4%). The most common diagnosis was diffuse otitis externa, 291 patients (86.9%). Most macroscopic features were hyperemic